Nitric Oxide–cGMP Pathway Modulation in an Experimental Model of Hypoxic Pulmonary Hypertension. (November 2021) - Reinero, Melanie; Beghetti, Maurice; Tozzi, Piergiorgio; Segesser, Ludwig K. von; Samaja, Michele; Milano, Giuseppina
Manipulation of nitric oxide (NO) may enable control of progression and treatment of pulmonary hypertension (PH). Several approaches may modulate the NO-cGMP pathway in vivo. Here, we investigate the effectiveness of 3 modulatory sites: (i) the amount ofl -arginine; (ii) the size of plasma NO stores that stimulate soluble guanylate cyclase; (iii) the conversion of cGMP into inactive 5′-GMP, with respect to hypoxia, to test the effectiveness of the treatments with respect to hypoxia-induced PH. Male rats (n = 80; 10/group) maintained in normoxic (21% O2 ) or hypoxic chambers (10% O2 ) for 14 days were subdivided in 4 sub-groups: placebo, l -arginine (20 mg/ml), the NO donor molsidomine (15 mg/kg in drinking water), and phoshodiesterase-5 inhibitor sildenafil (1.4 mg/kg in 0.3 ml saline, i.p.). Hypoxia depressed homeostasis and increased erythropoiesis, heart and right ventricle hypertrophy, myocardial fibrosis and apoptosis inducing pulmonary remodeling. Stimulating anyone of the 3 mechanisms that enhance the NO-cGMP pathway helped rescuing the functional and morphological changes in the cardiopulmonary system leading to improvement, sometimes normalization, of the pressures. None of the treatments affected the observed parameters in normoxia. Thus, the 3 modulatory sites are essentially similar in enhancing the NO-cGMP pathway, thereby attenuating the hypoxia-related effects that lead to pulmonary hypertension.